Strategi Pemberitaan Radar Jember dalam Menghadapi Digitalisasi Informasi - Wildatuzzakiah Wildatuzzakiah (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Radar Jember is a local mass media that has to survive in the midst of digitalization of information and the competition among other local mass media. As remember, the fate of mass media is the cutting of edge. So, they have to stay alive. This problem is worth to researching. Because to make the media stay alive is need the right strategy. The focus of this problem are 1) What are the factors that faces Radar Jember in the midst of digitalization of information?, 2) What is the news strategy used by manager to maintain Radar Jember in the midst of digitalization of information? The purpose of this study is to find out the factors and the news strategy that used to maintain Radar Jember media in the midst of digitalization of information. To identify the problem, this research used a qualitative method with data collection techniques, that is purposive sampling and snowball sampling. And the data obtained by interviews, observation, and documentation. The result of this research are 1) Radar Jember launch radarjember.id as a media evolution from analog to digital (multi-format) and online (internet based), 2) Radar Jember using website, Instagram and Youtube to publish news with a friendly style to the Jember audience, 3) Radar Jember also using SEO (Search Engine Optimization), Google News Trend, Tagging and Virtual Event, 4) Optimizing the code of ethic journalism, journalistic competence and trying to fulfill the information needs of audience, 5) Improving the quality of news segmentation, news angles, friendly language style for Instagram & Youtube and use formal language for website.